Accounting Information Systems in Religious Institutions: A Systematic Literature Review - Roy Mandagi; Raymond Manopo; Elvis Ronald Sumanti (Publikasi Indonesia, 2024)
This systematic literature review examines the design, implementation, and evaluation of accounting information systems (AIS) in religious institutions, focusing on mosques and churches. The review synthesizes findings from English and Bahasa Indonesia sources to identify common themes, challenges, and best practices in AIS development within religious contexts. A comprehensive search strategy was employed, guided by predefined criteria, to select relevant studies published between 2014 and 2024. Key findings highlight the importance of AIS in enhancing financial transparency, accountability, and efficiency in religious organizations. The review also identifies gaps in existing research and provides recommendations for future studies in this area.